Exploiting Genomics Resources to Identify Candidate Genes Underlying Antioxidants Content in Tomato Fruit - Calafiore, Roberta; Ruggieri, Valentino; Raiola, Assunta; Rigano, Maria M.; Sacco, Adriana; Hassan, Mohamed I.; Frusciante, Luigi; Barone, Amalia (Frontiers in Plant Science, 2016)
The tomato is a model species for fleshy fruit development and ripening, as well as for genomics studies of others Solanaceae. Many genetic and genomics resources, including databases for sequencing, transcriptomics and metabolomics data, have been developed and are today available. The purpose of the present work was to uncover new genes and/or alleles that determine ascorbic acid and carotenoids accumulation, by exploiting one Solanum pennellii introgression lines (IL7-3) harboring quantitative trait loci (QTL) that increase the content of these metabolite in the fruit. The higher ascorbic acid and carotenoids content in IL7-3 was confirmed at three fruit developmental stages. The tomato genome reference sequence and the recently released S. pennellii genome sequence were investigated to identify candidate genes that might control ascorbic acid and carotenoids accumulation. First of all, a refinement of the wild region borders in the IL7-3 was achieved by analyzing CAPS markers designed in our laboratory. Afterwards, six candidate genes associated to ascorbic acid and one with carotenoids metabolism were identified exploring the annotation and the Gene Ontology terms of genes included in the region. Variants between the sequence of the wild and the cultivated alleles of these genes were investigated for their functional relevance and their potential effects on the protein sequences were predicted. Transcriptional levels of candidate genes in the introgression region were extracted from RNA-Seq data available for the entire S. pennellii introgression lines collection and verified by Real-Time qPCR. Finally, seven IL7-3 sub-lines were genotyped using 28 species-specific markers and then were evaluated for metabolites content. These analyses evidenced a significant decrease in transcript abundance for one 9-cis-epoxycarotenoid dioxygenase and one L-ascorbate oxidase homolog, whose role in the accumulation of carotenoids and ascorbic acid is discussed. Comprehensively, the reported results demonstrated that combining genetic and genomic resources in tomato, including bioinformatics tools, was a successful strategy to dissect one QTL for the increase of ascorbic acid and carotenoids in tomato fruit.